Aspectos clínicos, laboratoriais e de imagem de cães criticamente enfermos com injúria renal aguda e sua relação com a pancreatite aguda. - Daniela Bastos de Souza Karam Rosa (2019)
The critically ill patient with acute renal failure is one of the most frequent in the hospitalization sector of the veterinary hospitals and its mortality rate is high. Chronic kidney disease dogs have also been frequent in the clinical routine. Both patients may present in a situation of hypercatabolism and negative energetic balance that associated with the uremia, generates a series of disorders to the organism, among them the possibility of acute pancreatitis. Clinical, laboratory and imaging parameters of 30 dogs with acute renal failure and their laboratory parameters were compared to healthy dogs and stable chronic renal patients, and these were the objectives of this study. Data were subjected to multivariate statistical analysis. It was possible to observe that in patients with acute renal failure the most frequent sonographic finding was hyperechogenicity of the renal cortical and the ultrasound sensitivit for detecting acute pancreatitis was low. Anorexia was present in almost all the dogs and the oliguria/anuria was directly related to a higher chance of death. The hematocrit had no direct correlation with the degree of uremia. There was a higher serum concentration of -hydroxybutyrate in patients with acute renal failure and a strong correlation between serum creatinine concentration and specific canine pancreatic lipase activity, demonstrating the possibility of development of acute pancreatitis in these patients.